2020
DOI: 10.1093/gji/ggaa260
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced magnetic fields within a stratified layer

Abstract: SUMMARY Mounting evidence from both seismology and numerical experiments on core composition suggests the existence of a layer of stably stratified fluid at the top of Earth’s outer core. In such a layer, a magnetostrophic force balance and suppressed radial motion lead to stringent constraints on the magnetic field, named Malkus constraints, which are a much more restrictive extension of the well known Taylor constraints. Here, we explore the consequences of such constraints for the structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…A rough estimate for the relative importance of toroidal BT and radial Br magnetic fields in the dynamics is mBTH/(Br0.17emR), where R is the radius of the core. Recent suggestions of strong toroidal fields in a stratified layer (Hardy et al., 2020) could make the toroidal field more important than expectations based on geodynamo models, although we do not consider this possibility here. Instead we adopt a constant rms radial field of 0.62 mT to be consistent with geodetic constraints (Koot et al., 2010).…”
Section: Signature Of Magnetic Rossby Wavesmentioning
confidence: 89%
“…A rough estimate for the relative importance of toroidal BT and radial Br magnetic fields in the dynamics is mBTH/(Br0.17emR), where R is the radius of the core. Recent suggestions of strong toroidal fields in a stratified layer (Hardy et al., 2020) could make the toroidal field more important than expectations based on geodynamo models, although we do not consider this possibility here. Instead we adopt a constant rms radial field of 0.62 mT to be consistent with geodetic constraints (Koot et al., 2010).…”
Section: Signature Of Magnetic Rossby Wavesmentioning
confidence: 89%
“…Thus, we need to scrutinise the influences of the critical latitudes on eigenmodes. Lastly, Hardy et al (2020) reported that slight vertical motions under strong stratification can enhance toroidal fields because of the "Malkus constraint." This suggestion supports our choice as a reasonable main field.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of stratification and/or precipitation has important implications for the dynamics and evolution of the core. Stratified layers suppress radial motion and may support strong toroidal fields (Hardy et al, 2020) and distinct classes of wave motions (Braginsky, 1999) that are observed as periodic variations of the geomagnetic field (Buffett, 2014;Buffett et al, 2016). Such a layer also acts to filter the field that is generated in the bulk core (Christensen, 2006;Gastine et al, 2020), effectively filtering our view of the dynamo process, which is primarily based on observations that only probe CMB field.…”
Section: Introductionmentioning
confidence: 99%